Politik Hukum Partisipasi Perempuan dalam Pilkades: Analisis Strategi Politik Kepala Desa di Desa Sutojayan Kecamatan Pakisaji Kabupaten Malang - Dafis Ubaidillah Assiddiq; Dewi Ambarwati; Syahrul Mubaroq; Moh Imron (Journal of Governance Innovation, 2025)
Leadership at the village level plays a strategic role in determining the direction of development, public services, andcommunity empowerment. Although the position of village head is generally held by men, the success of women in leadingvillages has become an interesting phenomenon to study, as seen in Sutojayan Village, Pakisaji District, Malang Regency. SitiRukhoiyah, the only female village head in the district, has served for three consecutive terms and managed to maintain her position through effective political marketing strategies and inspiring leadership. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and documentation, involving informants such as the village head, village officials, community leaders, and residents. The analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. The findings show that Siti Rukhoiyah’s political marketing strategy during her 2019 candidacy had several advantages, including her educational background (Bachelor’s degree in Law from the University of Muhammadiyah Malang), nearly 20 years of experience in leading the village, her family’s reputation— particularly the respected name of her late father, who also served as a village head—and her extensive social network in Sutojayan Village. The strategies implemented included a personal approach, particularly toward women, who were considered to have significant influence in directing family voting decisions, aswell as leveraging her positive image from active involvement in women’s organizations such as PKK and Muslimat. Although she initially faced resistance from the patriarchal culture, including opposition from some religious leaders, Siti Rukhoiyah was able to demonstrate firm, disciplined, participatory leadership with a maternal touch. She provided rewards forvillage officials in the form of annual recreational activities to motivate performance and was directly involved in various governmental activities, which made her perceived as more diligent and serious compared to her male predecessors. Herleadership also contributed to increasing women’s participation in the village, especially in the field of education, where women now dominate positions as teachers and heads of formal and informal educational institutions. In conclusion, Siti Rukhoiyah’s success in maintaining her position for three consecutive terms cannot be separated from theapplication of political marketing strategies based on cultural and gender approaches, as well as a leadership style thatcombines firmness, discipline, and care. This has succeeded in changing community perceptions and inspiring active participation of women in Sutojayan Village. Keywords: female village head, political marketing strategy, village leadership, women’s empowerment, community participation.